Pelatihan Merancang Soal Literasi Membaca Menggunakan ChatGPT untuk Guru-Guru di SMAN 2 Tapung Hilir - Mukhlis, Muhammad; Latif, Latif; Asnawi, Asnawi; Devi, Sylvia Pratama (UIR Press, 2023)
This service aims to improve the quality of student literacy learning at SMAN 2 Tapung Hilir through training in designing reading literacy questions using ChatGPT. Training includes a basic understanding of ChatGPT, techniques for designing effective questions, and utilizing relevant ChatGPT features. Through the training stages, teachers demonstrate their ability to apply newly acquired knowledge. Hands-on practice using ChatGPT provides valuable experience, with guidance from resource persons to ensure in-depth understanding. Group discussions and question and answer sessions facilitate the exchange of experiences and ideas among participants. Next, the practice and assessment stages provide opportunities for teachers to test their understanding through concrete practice tasks. Assessment of the quality of questions and constructive feedback strengthens the learning process. The results of the questionnaire showed a high level of satisfaction from participants, illustrating that this training provided significant benefits for teachers